ANALISIS EKOLINGUISTIK PADA PANTUN MELAYU DELI - Nur Indah Yusari; Dewi Sari Sumitro; Sri Rosmalina Soedjono; Lilik Herawati (JENTERA: Jurnal Kajian Sastra, 2025)
This study analyzes the ecological representation, ecological meaning, and function of Deli Malay pantun through an ecolinguistic approach. The data, consisting of Deli Malay pantun, were examined using content analysis of three linguistic units: lexicon, semantics, and pragmatics. Lexical analysis shows that pantun contains a lexicon of flora, fauna, ecological landscapes, and natural phenomena that reflect the Malay people's closeness to the agrarian environment and tropical forests. At the semantic level, these ecological elements contain symbolic and metaphorical meanings that construct ecological stories, such as hope, vulnerability, and human-nature balance. Pragmatically, pantun functions as an instrument of cultural communication in customs, moral education, and the formation of social ethics. Ecolinguistic synthesis reveals that Deli Malay pantun serves as an ecological cultural archive that stores environmental knowledge while affirming the ecological identity of the Malay people. This study confirms that pantun is not only aesthetically valuable but also serves as a medium for transmitting ecological wisdom relevant to cultural and environmental preservation. Abstrak Penelitian ini menganalisis representasi ekologis, makna ekologis, dan fungsi pantun Melayu Deli melalui pendekatan ekolinguistik. Data berupa pantun Melayu Deli dikaji dengan analisis konten terhadap tiga unit linguistic, yaitu leksikon, semantik, dan pragmatik. Analisis leksikal menunjukkan bahwa pantun memuat leksikon flora, fauna, lanskap ekologis, dan fenomena alam yang mencerminkan kedekatan masyarakat Melayu dengan lingkungan agraris dan hutan tropis. Pada tataran semantik, unsur ekologis tersebut memuat makna simbolik dan metaforis yang membangun ecological stories, seperti harapan, kerentanan, dan keseimbangan manusia–alam. Secara pragmatik, pantun berfungsi sebagai instrumen komunikasi budaya dalam adat, pendidikan moral, dan pembentukan etika sosial. Sintesis ekolinguistik mengungkap bahwa pantun Melayu Deli berperan sebagai arsip ekologis budaya yang menyimpan pengetahuan lingkungan sekaligus meneguhkan identitas ekologis masyarakat Melayu. Penelitian ini menegaskan bahwa pantun tidak hanya bernilai estetis, tetapi juga menjadi medium pewarisan kearifan ekologis yang relevan bagi pelestarian budaya dan lingkungan.